Analisis RPP Kurikulum 2013 Dengan Modul Ajar Kurikulum Merdeka Belajar Mata Pelajaran Bahasa Dan Sastra Indonesia Kelas VII Di SMP Adhyaksa Medan - Manurung, Florentina Br; S, Monalisa Frince; Saragih, Renita Br (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research aims to provide data descriptions regarding the differences in content between the 2013 Curriculum RPP and the Independent Learning Curriculum Teaching Module for Class VII Indonesian Language and Literature Subjects at Adhyaksa Middle School Medan. This type of research is qualitative descriptive research. This approach is carried out by analyzing the words or text contained in the object to be studied. After analyzing the 2013 curriculum lesson plan and the independent curriculum teaching module, differences between the two were obtained. These differences cover several aspects, including identity, initial components, profile of Pancasila students, facilities and infrastructure, target students, learning models, assessments, meaningful understanding, trigger questions, enrichment and remedial, reading materials for educators and students, glossaries and lists. References. The Merdeka Curriculum Teaching Module emphasizes recognition of the intellectual contribution of learning material compilers, transparency, recognition of changes in learning approaches, deepening students' understanding, and active involvement of students in the learning process. These changes are based on government policies that face the latest educational challenges, such as adaptation during the COVID-19 pandemic and adjustment to updated competency standards. These differences indicate an evolution in approaches and priorities in preparing learning materials, as well as efforts to improve the overall quality of education.